2014
DOI: 10.1097/ta.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage depletion increases the severity of acute inflammation following nonlethal unilateral lung contusion in mice

Abstract: BACKGROUND Lung contusion (LC) is a common injury resulting from blunt thoracic trauma. LC is an important risk factor for the development acute lung injury, adult respiratory distress syndrome, and ventilator-associated pneumonia, all of which increase mortality from trauma. LC produces a nonspecific immune cellular response. Neutrophil recruitment is known to increase the severity of inflammation during LC. However, the exact role of macrophages in modulating the response to LC has not been well described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…One feature includes the reduction in apoptosis of the alveolar macrophage, a cell that plays a protective role in the resolution of inflammation(19), and this is a finding similar to observations in hyperoxia(29). The second mechanism involves the TLR3 driven change in polarization of the macrophage.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…One feature includes the reduction in apoptosis of the alveolar macrophage, a cell that plays a protective role in the resolution of inflammation(19), and this is a finding similar to observations in hyperoxia(29). The second mechanism involves the TLR3 driven change in polarization of the macrophage.…”
Section: Discussionmentioning
confidence: 69%
“…We have previously shown that the acute inflammatory response in LC is responsible for deficits in oxygenation and increases in quasi-static pulmonary compliance and severe permeability injury (BAL albumin)(8, 16–19). While there was a significant decrease in the BAL albumin level in TLR3 (−/−) mice (Figure 2a), pulmonary compliance and volumes were significantly lower in WT mice (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…3,9,13,16,18 In the present study, we propose ODD-Luc mice as a novel model of LC. Global hypoxia developed after LC and was most pronounced in the liver and spleen.…”
Section: Discussionmentioning
confidence: 95%
“…This overall profile of inflammation and injury is consistent with that demonstrated in previous mouse and rodent models, substantiating ODD-Luc mice as a viable model for LC. 3,9,13,16,18 …”
Section: Resultsmentioning
confidence: 99%
“…In the absence of resident AM, Fasinduced lung damage was worsened [21], displayed by significantly increased BAL protein concentration and lung histology. Furthermore, depletion of AM increased lung damage and inflammation following non-lethal unilateral lung contusion in mice [109]. The protective effects of neutrophil depletion fall into place particularly in synopsis with the exacerbation of lung injury in the absence of AM as a result of deficient phagocytosis and reduced degradation of apoptotic PMN [92].…”
Section: Apoptosismentioning
confidence: 99%